The Validity of Single Candidates in Regional Head Elections - Chusnul Khitam, Muhammad; Faizah, Niswatun; Shodiq, Ja’far; Khuluq, Muhammad Husnul (Universitas Islam Lamongan, 2026)
Democracy is a system where the people as the holders of the highest power have the right in all decision-making that includes the interests of the people in a region. In this case, indirectly the people can also issue laws and regulations that are beneficial and also to protect their rights. The 1945 Constitution of the Republic of Indonesia, Article 1 paragraph (2) of the 1945 Constitution which reads